Nova metodologia para identificação de pontos críticos de desempenho em linhas de transmissão baseada na aplicação de sistemas de localização de descargas atmosféricas - Rosilene Nietzsch Dias (2006)
The modern Lightning Location Systems (LLS) are the most advanced tool to provide lightning data in a wide scale range. Despite the LLS potentiality, the use of LLS data to support the design and operation activities in electric power systems is still relatively poor. In this work an original methodology was developed. It explores the application of LLS data combined to evaluations based on transmission line data to define critical spots along the line in terms of lightning performance. This allows determining the structures (towers or poles) where protection investments are recommended. The methodology is based on the determination of backflashover risk for each transmission line structure. The methodology was applied to real transmission lines and good results were achieved.